2008 IEEE Nuclear Science Symposium Conference Record 2008
DOI: 10.1109/nssmic.2008.4774602
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Undoped NaI Scintillators with Different Purity

Abstract: The performance of undoped NaI crystal of a high purity of 7 N grade, developed by Saint-Gobain Crystals for a dark matter search, was studied at liquid nitrogen temperature using avalanche photodiode. The measured quantities covered the light output expressed in the electron-hole (e-h) pair number, non-proportionality characteristics, energy resolution and tinally the intrinsic resolution of the studied crystals. In contrast to the previous study, the new crystals showed comparable non-proportionality curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 35 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…Moszyń ski et al, 2009). A similar effect observed in the undoped CsI(Moszyń ski et al, 2005c) suggested that accidental doping by impurities improved seriously a non-proportionality and then the energy resolution.Moreover, several observations collected in the last 10 years on the unexpected influence of slow components of the light pulses on energy resolution suggest more complex processes in the scintillators.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…Moszyń ski et al, 2009). A similar effect observed in the undoped CsI(Moszyń ski et al, 2005c) suggested that accidental doping by impurities improved seriously a non-proportionality and then the energy resolution.Moreover, several observations collected in the last 10 years on the unexpected influence of slow components of the light pulses on energy resolution suggest more complex processes in the scintillators.…”
mentioning
confidence: 59%
“…The non-proportionality of the undoped oxide crystals, as BGO (Moszyń ski et al, 2004) and CWO (Moszyń ski et al, 2005a), represents the fundamental properties of the scintillator materials. In case of doped crystals, one observes variation of the non-proportionality characteristic depending on doping agents, particularly for halide crystals (Moszyń ski et al, 2009(Moszyń ski et al, , 2005c. Moreover, the pure, undoped halide crystals, as NaI and CsI, are very sensitive to the impurities, which affect the non-proportionality curves (Moszyń ski et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some traces of OH -, H -, CO 3 2-, O 2 2-are always present even in "pure" [11,12] and Tl-doped NaI crystals [13,[17][18][19]. In some crystals which are "nominally pure" scintillators non-proportionality of the intrinsic emission cannot be properly justified [20]. The total content of the oxygen ions and oxygencontaining impurities in NaI:Eu crystal may be comparable with the concentration of the Eu 2+ ions.…”
Section: Discussionmentioning
confidence: 99%